Whole-chromosome fusions in the karyotype evolution of Sceloporus (Iguania, Reptilia) are more frequent in sex chromosomes than autosomes - Lisachov, Artem P. (Philos Trans R Soc Lond B Biol Sci, 2021)
Whole-chromosome fusions play a major role in the karyotypic evolution of reptiles. It has been suggested that certain chromosomes tend to fuse with sex chromosomes more frequently than others. However, the comparative genomic synteny data are too scarce to draw strong conclusions. We obtained and sequenced chromosome-specific DNA pools of Sceloporus malachiticus, an iguanian species which has experienced many chromosome fusions. We found that four of seven lineage-specific fusions involved sex chromosomes, and that certain syntenic blocks which constitute the sex chromosomes, such as the homologues of the Anolis carolinensis chromosomes 11 and 16, are repeatedly involved in sex chromosome formation in different squamate species. To test the hypothesis that the karyotypic shift could be associated with changes in recombination patterns, we performed a synaptonemal complex analysis in this species and in Sceloporus variabilis (2n = 34). It revealed that the sex chromosomes in S. malachiticus had two distal pseudoautosomal regions and a medial differentiated region. We found that multiple fusions little affected the recombination rate in S. malachiticus. Our data confirm more frequent involvement of certain chromosomes in sex chromosome formation, but do not reveal a connection between the gonosome–autosome fusions and the evolution of recombination rate. This article is part of the theme issue ‘Challenging the paradigm in sex chromosome evolution: empirical and theoretical insights with a focus on vertebrates (Part II)’.